Why Finance Ministers Favor Carbon Taxes, Even if They Do not Take Climate Change into Account - Max Franks; Ottmar Edenhofer; Kai Lessmann (Fondazione Eni Enrico Mattei (FEEM), 2015)
Fiscal considerations may shift governmental priorities away from environmental concerns: Finance ministers face strong demand for public expenditures such as infrastructure investments but they are constrained by international tax competition. We develop a multi-region model of tax competition and resource extraction to assess the fiscal incentive of imposing a tax on carbon rather than on capital. We explicitly model international capital and resource markets, as well as intertemporal capital accumulation and resource extraction. While fossil resources give rise to scarcity rents, capital does not. With carbon taxes the rents can be captured and invested in infrastructure, which leads to higher welfare than under capital taxation. This result holds even without modeling environmental damages. It is robust under a variation of the behavioral assumptions of resource importers to coordinate their actions, and a resource exporter's ability to counteract carbon policies. Further, no green paradox occurs - instead, the carbon tax constitutes a viable green policy, since it postpones extraction and reduces cumulative emissions.
Keywords: F21; H21; H30; H73; Q38; 330; Carbon Pricing; Green Paradox; Infrastructure; Optimal Taxation; Strategic Instrument Choice; Supply-Side Dynamics; Tax Competition